Mediating Role of Public Service Motivation in Enhancing the Effect of Spiritual Leadership on Felt Obligation and Affective Commitment - Hasrudy Tanjung; Nik Sarina Nik Md Salleh; Hafid Aditya Pradesa (Universitas Pendidikan Ganesha, 2023)
Encouraging positive feelings at work is important in a public organization. While leadership and motivation are recognized as things that can improve the positive form of individual attitudes and behavior among individuals. By integrating the concepts of leadership and motivation as determinants of employee attitudes, the purpose of this research is to analyze about how public service motivation could mediate the effect of spiritual leadership towards affective commitment and felt obligation. Quantitative method is used as a research deductive paradigm with a purposive sampling technique used to obtain 97 civil servants that take part as respondent in this study who work in two Government Agencies in the Province of North Sumatra, Indonesia. Findings indicate that five hypotheses proposed in the study were confirmed, but there was one relationship that was found to have an insignificant effect, which is the direct effect of spiritual leadership on felt obligation. Main implication of the findings reveals about the significant role of public service employee motivation in strengthening spiritual leadership in improving both affective commitment and felt obligation.